Sustaining Automated Library Systems in Academic Libraries: The Ghanaian Experience - Armah, Angelina Lily (Ghana Library Journal, 2000)
The last decade has seen academic libraries in Ghana on a steady move towards library  automation. Almost all the university libraries in Ghana are at least partially automated. Automation has greatly enhanced performance in library work and has provided improved services and user access to current information through the use of CD-ROMs, the Internet, Inter Library Lending and Document Delivery (ILL/DD) and email. But as much as this technology provides opportunities for enhanced performance and effective services, it has equally presented the challenge of sustainability. The issue at stake is how academic libraries can sustain their automated systems as they struggle to cope with limited resources and rapid increase in student numbers. Drawing from the experiences of the academic libraries in Ghana, this paper discusses various steps towards the sustainability of automated systems in the academic libraries in Ghana.